Fatores associados a sintomas depressivos em pacientes com doença cardiovascular internados no Hospital das Clínicas da UFMG - Felipe Jose Nascimento Barreto (2016)
Prevalence of depression is considerably higher among individuals with cardiovascular diseases (CVD) when compared to the general population. Both depression and presence of depressive symptoms increase cardiovascular mortality and predict poor general outcome for individuals with CVD. Although relationship between depression and CVD have been well established and studied worldwide on the past two decades, depression still is a frequently overlooked and untreated condition in individuals with CVD. The same is true for inpatients in general hospital, where less than one case of depression in four are treated properly. Understanding of which factors are more associated to presence of depressive symptoms may improve its screening in general hospital wards and, hence, aim for more specific therapeutic interventions among individuals with CVD. Objective: To identify factors associated to presence of depressive symptoms in inpatients with CVD. Methods: This is a cross-sectional study that assessed individuals aged 18 years or older who presented a diagnosis of CVD and were hospitalized in non-surgical wards of the university hospital of UFMG from November 2013 to October 2015. Sociodemographic and clinical data were obtained through interview with subjects and medical report review. Presence of depressive symptoms was assessed by the depression subscale of the Hospital Anxiety and Depression Scale (HADS-d), with scores greater than or equal to 8 suggestive of positive screening for depression. Other instruments were applied, namely: Katz Index, Pffeffers Functional Activities Questionnaire, visual scale for pain, Confusion Assessment Method, Montreal Cognitive Assessment, Alcohol Use Disorders Identification Test, Fageström Test for Nicotine Dependence, Wagnild & Young Resilience Scale and Childhood Trauma Questionnaire. Results: In the studied sample, thirty-eight (27,7%) subjects had depressive symptoms (HADS-d score 8). Among them, nine (23,7%) were receiving some antidepressant treatment during its hospitalization. According to multivariated analysis, moderate to severe nicotine dependence (OR=8,58; p=0,008), number of previous hospital admissions, (OR= 1,11; p=0,034) and higher childhood trauma severity (OR=1,06; p= 0,004) were factors independently associated with the presence of depressive symptoms. The obtained logistic model was considered valid, indicating that the three factors together distinguished between having or not depressive symptoms, and correctly classified 74.6% of individuals in the sample. Conclusion: Results of our study underscore the importance of clinically available factors that make CVD inpatients more prone to have depressive symptoms while in general hospital